2007
DOI: 10.1007/s00442-007-0923-8
|View full text |Cite
|
Sign up to set email alerts
|

Explaining variation in tropical plant community composition: influence of environmental and spatial data quality

Abstract: The degree to which variation in plant community composition (beta-diversity) is predictable from environmental variation, relative to other spatial processes, is of considerable current interest. We addressed this question in Costa Rican rain forest pteridophytes (1,045 plots, 127 species). We also tested the effect of data quality on the results, which has largely been overlooked in earlier studies. To do so, we compared two alternative spatial models [polynomial vs. principal coordinates of neighbour matric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
204
6
17

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 191 publications
(250 citation statements)
references
References 55 publications
20
204
6
17
Order By: Relevance
“…A study in four Amazonian forest sites by Tuomisto and Poulsen (2000) found similarity values close to the ones in this study, between 47% and 58%, but the areas were up to 600 km apart. Such a distinction could be associated to differences in topography of the Atlantic and Amazon forests (Vormisto et al 2004, Jones et al 2006, 2008. The Atlantic forest is known for its wide range distribution along the Brazilian coast, presenting a quite variable topography and thus a broad array of environmental factors (Oliveira-Filho and Fontes 2000, Tonhasca Jr. 2005, Nettesheim et al 2010.…”
Section: Species Compositionmentioning
confidence: 99%
See 4 more Smart Citations
“…A study in four Amazonian forest sites by Tuomisto and Poulsen (2000) found similarity values close to the ones in this study, between 47% and 58%, but the areas were up to 600 km apart. Such a distinction could be associated to differences in topography of the Atlantic and Amazon forests (Vormisto et al 2004, Jones et al 2006, 2008. The Atlantic forest is known for its wide range distribution along the Brazilian coast, presenting a quite variable topography and thus a broad array of environmental factors (Oliveira-Filho and Fontes 2000, Tonhasca Jr. 2005, Nettesheim et al 2010.…”
Section: Species Compositionmentioning
confidence: 99%
“…Despite its variable terrain and habitat heterogeneity, the Amazon forest can be considered to have a rather plain topography and mild collection of environmental factors when compared to its eastern close relative, the Atlantic forest (Rizzini 1997, Tuomisto et al 2003a. Perhaps, the low ferns and lycophytes similarity values between the Marambaia paleoisland slopes is a consequence of the topographic heterogeneity of this forest (Tuomisto et al 2002, Karst et al 2005, Jones et al 2006, 2008, Nettesheim et al 2010.…”
Section: Species Compositionmentioning
confidence: 99%
See 3 more Smart Citations